A New Species of Red-eyed frog of the genus Pristimantis (Anura: Strabomantidae) from the Western Slope of the Cordillera Occidental, Risaralda, Colombia - Duarte-Marín, Sebastián; Montoya-Marín, Manuela; Rivera-Gómez, Jackeline (Zootaxa, 2022)
We describe a new species of red-eyed frog of the genus Pristimantis from the tropical forest at elevations of 1000–1350 m on western slope of the Cordillera Occidental, department of Risaralda, Colombia. The new species differs from congeners by having dorsum skin shagreened with low tubercles; vocal sac single, median and subgular in males, iris red wine in females copper red in males, and by presenting black groin coloration with yellow light blotches. In addition, the new species has concave frontoparietals, an unusual character described in Brachycephaloidea frog species.